Inclusion of Children with Special Needs (CWSN) and School Leadership: A Review - Sharma, Indu (JOURNAL OF INDIAN EDUCATION, 2022)
Globally, a school entails diversity and is not situated within one kind of uniform structure of society. Diversity in schools could be due to differences in class, gender, socio-economic strata, race, disability, caste, region, language, ethnicity, and so on. At national and international levels both, the robust call for school reform led to their all governments to focus efforts on inclusive education. Children with special needs (CWSN) are no exception to exercising their right to avail themselves of educational provisions as per their individual needs. The focus of diversity in this paper, for inclusion in the school context, is CWSN. The school head as the vital stakeholder in the teaching=learning process has to constantly find pathways to meet these challenges daily in the school set up especially in post Covid-19 times. The paper reviews the interface of school leadership and inclusion of CWSN.